Religion: Colonizers and Others - Syed Aziz; Dr. Bilal Ahmad (Journal of Religion and Society, 2026)
The study centers on Christianity as a tool of imperial expansion within the Spanish, Portuguese, French, and British empires, showing how colonizers positioned their religion as divinely sanctioned and culturally superior. By highlighting Christopher Columbus’s apocalyptic worldview and the missionary strategies that followed, the abstract demonstrates how colonizers framed conquest as a sacred obligation, thereby legitimizing domination over “others” defined by different belief systems. In this framework, religion was not merely a spiritual concern but a foundational element of imperial ideology, shaping political authority, legal systems, and social hierarchies in newly conquered territories. By comparing native belief systems ranging from animism and ancestor veneration to complex cosmologies and organized priesthoods with the mechanisms of forced conversion, religious destruction, educational reform, and missionary governance, the research demonstrates how Christianity functioned simultaneously as a justification for conquest and as an instrument for restructuring colonized societies. Mission institutions became central sites for redefining cultural norms, moral values, and communal identities according to European Christian standards. The findings show that while Christianization significantly altered global religious landscapes, indigenous communities responded through resistance, adaptation, and syncretism, reshaping imposed doctrines within their own cultural frameworks. These processes produced new hybrid religious identities that reflect both colonial influence and indigenous continuity, illustrating how the encounter between colonizers and “others” transformed religious life on a global scale and left enduring legacies in the modern world. Keywords: Christianization, Colonization, Indigenous Religions, Missionary Expansion, Spanish Empire, Portuguese Empire, French Empire and British Empire.